الدور الحضاري للمرأة بين الإسلام والمسيحية - حنيش, نورة (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2023)
قمنا في هذه الدراسة العلمية التحليلية بدراسة موضوع الدور الحضاري للمرأة بين الإسلام والمسيحية (دراسة في ضوء الواقع الإسلامي والواقع الغربي)، وقد حددت إشكالية الدراسة بالصيغة التالية: ما هي أهم الأدوار الحضارية التي قامت بها المرأة المسلمة بالمقارنة مع المرأة المسيحية في الواقع الإسلامي والواقع الغربي؟ إن إشكالية الدراسة التي تطرح نفسها عند محاولة تكوين رؤية معاصرة حول أدوار المرأة المسلمة اليوم، ومجموع التساؤلات التي تثيرنا حول موضوع المرأة في عالمنا المعاصر وعلاقتها بالمشكلات الحضارية، دفعت بنا نحو هذه الدراسة التي انطلقنا فيها من المقارنة بين أهم الأدوار الحضارية التي قامت بها المرأة المسلمة مقارنة بما قدمته المرأة المسيحية في العالم الغربي، هذه المقارنة التي اعتمدنا فيها على المرجعية الدينية التي تنطلق من النص الديني" الإنجيل- القرآن الكريم والسنة الشريفة"، باعتبار النص الديني المرجع الأول لحركة المرأة في المجتمع، وصولا بنا إلى تطلعات التيارات الفكرية حول قضايا المرأة في العالمين الإسلامي والغربي، لنقوم بتقديم عرض موجز يوضح لنا معالم الرؤية الحضارية لكل نموذج، وأهم المعيقات التي تعرض لها كل نموذج حسب خصائص كل مجتمع، لنصل في ختام هذه الدراسة لأهم الأدوار التي يمكن للمرأة المسلمة أن تقوم بها أثناء رسالتها الحضارية، مؤكدين على ضرورة صناعة ظروف اجتماعية وسياسية وثقافية ودينية وحتى أمنية، تمكن المرأة من العمل بفاعلية لخدمة قضايا الأمة ودعوة التوحيد، انطلاقا من واجبها الحضاري كما يقول ابن نبي" الذي يستدعيها أن توضع هنا وهناك حتى تؤدي دورها خادمة للحضارة، وملهمة لذوق الجمال وروح الأخلاق، ذلك الواجب الذي بعثها الله فيه أما وزوجة للرجل"، وتتلخص أهداف هذه الدراسة في البحث عن معالم النموذج الإسلامي المحض لصورة المرأة المسلمة القائمة على خدمة رسالة الإسلام العالمية، محاولين بذلك نفض الغبار عن أبعاد تلك الصورة الحضارية من عمق التاريخ الإسلامي والمسيحي والتي مثلتها المرأة المؤمنة والمسلمة في القرآن الكريم والسنة النبوية الشريفة، وقدمها عيسى -عليه السلام - في الإنجيل، بعد أن تلاشت واندثرت ملامحها في واقعنا المعاصر، وللوصول لأهداف الدراسة قمنا بتوظيف المنهج المقارن والمنهج الاستقرائي، الذي مكننا من الحصول على النتائج العامة والخاصة للدراسة، والبحث حول أهم الفروقات العملية والعلمية التي ميزت بين التجربتين، كما وظفنا المنهج التحليلي لعرض أهم الأفكار التي تبناها أصحاب المشاريع الفكرية في العالمين الإسلامي والغربي، لنصل في نهاية الدراسة إلى تحديد معالم الأدوار الحضارية للمرأة من خلال النص الديني، وأهم الأدوار الحضارية التي قامت بها المرأة المسلمة والغربية المسيحية في واقعنا المعاصر، لنصل في نهاية دراستنا لطرح تساؤل جوهري عن مدى درجة وعي المرأة المسلمة بثقل واجباتها الحضارية تجاه المجتمع الإسلامي والإنساني في ظل الأزمات والتحديات التي تعيشها الإنسانية اليوم ؟ Abstract In this analytical scientific study, we studied the subject of the civilized role of women between Islam and Christianity (a study in the light of the Islamic reality and the Western reality), it has identified a problem of the study is as follows: What are the most important civilized roles played by Muslim women that Compared to Christian women in the Islamic and Western realities? The problematic study that presents itself when trying to form a contemporary vision about the roles of Muslim women today, and the sum of the questions that raise us about the subject of women in our world contemporary and its relationship to civilizational problems pushed us towards this study in which we launched from the comparison between the most important civilized roles played by Muslim women compared to what they presented Christian women in the Western world, this comparison in which we relied on the religious reference that It starts from the religious text of the Bible - the Holy Quran and the Sunnah, considering the religious text , the first reference for the women's movement in society, leading us to the aspirations of intellectual currents about women's issues in the Islamic and Western worlds, Let's make a brief presentation that shows us the landmarks of the civilized vision of each model, and the most important obstacles to which each model was exposed according to the characteristics of every society, let's reach at the end of this study the most important roles that Muslim women can play during its civilizational message, stressing the need to create social, political and cultural conditions religious and even security, enabling women to work effectively to serve the causes of the nation and call for monotheism, it based on its civilized duty, as the son of a prophet says, who calls for it to be placed here and there until she performs her role as a servant of civilization, an inspiration for the taste of beauty and the spirit of morality, a duty that God sent her as a mother and wife for the man, and the objectives of this study are summarized in the search for landmarks, The purely Islamic model of the image of Muslim women based on serving the message of Islam universality, thus trying to dust off the dimensions of that civilized image from the depth of history Islamic and Christian represented by believing and Muslim women in the Holy Quran and the Sunnah of the Prophet. the honorable one, and was presented by Jesus - peace be upon him - in the Bible, after it faded and disappeared its features in our Contemporary Reality, To reach the objectives of the study, we have employed the comparative approach and the method. Inductive, which enabled us to obtain the general and specific results of the study, and research on the most important practical and scientific differences that distinguished between the two experiments, and we also employed the analytical method to present the most important ideas adopted by intellectual entrepreneurs in the Islamic and Western worlds, At the end of the study, we will reach the definition of the features of the civilized roles of women through the religious text, and the most important civilized roles played by Muslim and Western Christian women in our Contemporary reality , let us arrive at the end of our study to ask a fundamental question about the degree of awareness of Muslim women with the weight of their civilized duties towards the Islamic and humanitarian community in light of crises and the challenges that humanity is experiencing today?
- دراسة في ضوء الواقع الإسلامي والواقع الغربي -
أطروحة دكتوراه تخصص دعوة وثقافة إسلامية في العلوم الإسلامية
Keywords: الدور، الحضارة، المرأة، الواقع الإسلامي، الواقع الغربي; role, civilization, women, Islamic reality, Western reality.